Estimation of supplemental irrigation for Aman rice cultivation in Bogra and Dinajpur districts of Bangladesh (Progressive Agriculture, 2017)
A study was carried out to analyze the rainfall and evapotranspiration for successful planning of two aman rice varieties i.e., BRRI dhan33 and BRRI dhan34 in Bogra and Dinajpur districts of Bangladesh. Reference crop evapotranspiration (ET0) was determined by employing the FAO Penman-Monteith method. By multiplying ET0by crop coefficient (Kc) actual evapotranspiration of the two rice varieties at different growth stages was determined. Probability analysis was done by Weibulls method and the expected rainfall and actual evapotranspiration at 75% probability level were estimated for different growth stages of BRRI dhan33 and BRRI dhan34 for 14 years. The results revealed that the ETc varied over the total growing season. After probability analysis, the supplemental irrigation was calculated for BRRI dhan33 during mid and late stages; but for BRRI dhan34, it was calculated during development, mid and late stages in Bogra and Dinajpur districts. The study was found quite effective to assess the water availability period for aman cultivation and to indicate when supplemental irrigation is necessary. These results may enable to optimize utilization of valuable water resources and will help to create an irrigation schedule for BRRI dhan33 and BRRI dhan34 for their successful cultivation.Progressive Agriculture 28 (1): 42-54, 2017